Immigrant Employment and the Contract Enforcement Costs of Offshoring - Andreas Hatzigeorgiou; Patrik Karpaty; Richard Kneller; Magnus Lodefalk (Global Labor Organization (GLO), 2022)
Offshoring continues to be an important dimension of firms' internationalization choices. However, offshoring also increases contract enforcement costs by inhibiting the coordination and monitoring of performance. Immigrant employees may reduce such costs through their specific knowledge of the employer, their country of birth and access to foreign networks. We develop a heterogeneous firm framework with immigrants and offshoring costs, including technology leakage. In the model, immigrant employees augment the supervisory services of headquarters and limit technology leakage, thereby reducing contract enforcement costs. Then, we bring our conjectures to rich administrative Swedish microlevel data that include specific information about the characteristics of employees, manufacturing firms and their bilateral offshoring. Our results support the hypothesis that immigrant employees increase offshoring intensity by lowering contract enforcement costs. Hiring one additional immigrant employee can increase offshoring by up to three percent on average, with the strongest effects found for skilled immigrant employees.
Keywords: F22; F23; F14; D21; D83; 330; Offshoring; contract enforcement; immigrant employees; networks; information